2020
DOI: 10.1177/2041669520982317
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Material Properties on the Perceived Shape of Three-Dimensional Objects

Abstract: Perceiving the shape of three-dimensional objects is essential for interacting with them in daily life. If objects are constructed from different materials, can the human visual system accurately estimate their three-dimensional shape? We varied the thickness, motion, opacity, and specularity of globally convex objects rendered in a photorealistic environment. These objects were presented under either dynamic or static viewing condition. Observers rated the overall convexity of these objects along the depth ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…We found that the thickness of objects with specular reflectance tends to be perceptually overestimated, and thickness of transparent objects tends to be perceptually underestimated. We also found that the objects with 50% specular and 50% transparent components were perceived to have similar thickness to that of 100% specular surfaces, as demonstrated in Figure 1 (Ohara et al, 2020 ). These results indicate that the specular component can dominate in the perception of 3D shape.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…We found that the thickness of objects with specular reflectance tends to be perceptually overestimated, and thickness of transparent objects tends to be perceptually underestimated. We also found that the objects with 50% specular and 50% transparent components were perceived to have similar thickness to that of 100% specular surfaces, as demonstrated in Figure 1 (Ohara et al, 2020 ). These results indicate that the specular component can dominate in the perception of 3D shape.…”
Section: Introductionsupporting
confidence: 75%
“…We have already found that the refractive component reduced thickness perception (Ohara et al, 2020). In contrast, the reflective component enhances thickness perception (Nishida and Shinya, 1998;Mooney and Anderson, 2014).…”
Section: Unnatural Stimulimentioning
confidence: 76%
See 1 more Smart Citation
“…This dynamic rendering may need to be implemented in a way that is also dependent on scene content. It is possible that the user's tolerance of linear sensory conflict may decline when a structured ground-plane is used, which could be exacerbated by the rendering of diffuse or specular reflectance properties informative of surface shape and gloss (Honson et al, 2020;Ohara et al, 2020). In these situations, it may be necessary to rely on rest frames to provide users with a stable physical frame of reference (Prothero, 1998).…”
Section: Suggested Design Guidelinesmentioning
confidence: 99%
“…That is, different individuals infer similar—but not identical—3D surfaces from the same image. There is a huge literature confirming this, sometimes emphasizing material or lighting influences and sometimes emphasizing over/underestimation of surface normals ( Sun & Schofield, 2012 ; Mamassian & Kersten, 1996 ; Mingolla & Todd, 1986 ; Todd et al, 2014 ; Egan & Todd, 2015 ; Christou & Koenderink, 1997 ; Egan & Todd, 2015 ; Seyama & Sato, 1998 ; Curran & Johnston, 1996 ; Khang et al, 2007 ; Koenderink et al, 1996 ; Marlow et al, 2015 ; Nishida & Shinya, 1998 ; Nefs et al, 2006 ; Vangorp et al, 2007 ; Ohara et al, 2020 ; Bernhard et al, 2016 ; Faisman & Langer, 2013 ). Since we are studying shape descriptions, we are working at a scale different from textures and surface coverings, and we are not seeking to estimate lighting directions (cf.…”
Section: Introductionmentioning
confidence: 96%